Mechanizmy pogłębiania komunikacji politycznej w układzie o stowarzyszeniu między Ukrainą a Unią Europejską - Krasiwski, Orest (Studia Europaea Gnesnensia, 2019)
The paper discusses the role of the Association Agreement in deepening political communication between Ukraine and the EU. The author highlights the role of political communication in shaping the political association between Ukraine and the EU, and analyzes instances of such communication within the frame-work of the Ukraine-EU summits, Association Council, Association Committee, Parliamentary Committee of the Association and Civil Society Platform is ana-lyzed. As a result, the chief issues affecting political communication between Ukraine and the EU are revealed.